2001
DOI: 10.1046/j.1365-294x.2001.01145.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of the land snail Helix aspersa in the Western Mediterranean: preliminary results inferred from mitochondrial DNA sequences

Abstract: Intraspecific phylogeographic methods provide a means of examining the history of genetic exchange among populations. As part of a study of the history of Helix aspersa in the Western Mediterranean, we performed a phylogenetic analysis based on partial sequences of the mitochondrial large ribosomal subunit (16S) gene. Our samples include 31 H. a. aspersa populations from North Africa previously investigated for anatomical and biochemical characters. To clarify subspecific relationships, three individuals of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 21 publications
8
73
0
2
Order By: Relevance
“…However, much less is understood concerning the evolutionary history of North African fauna during this period. North Africa experienced alternate humid and arid periods that appeared to affect many terrestrial species, from snails (Guiller et al, 2001) to mammals (Cosson et al, 2005). Of the reptiles studied, Agama (Brown et al, 2002), Acanthodactylus (Harris et al, 2004a), Blanus (Vaconcelos et al, 2006), Lacerta perspicillata (Harris et al, 2003) and Tarentola (Harris et al, 2004b) all show deep phylogenetic divisions, and the same is demonstrated here in U. acanthinura.…”
Section: Resultssupporting
confidence: 69%
“…However, much less is understood concerning the evolutionary history of North African fauna during this period. North Africa experienced alternate humid and arid periods that appeared to affect many terrestrial species, from snails (Guiller et al, 2001) to mammals (Cosson et al, 2005). Of the reptiles studied, Agama (Brown et al, 2002), Acanthodactylus (Harris et al, 2004a), Blanus (Vaconcelos et al, 2006), Lacerta perspicillata (Harris et al, 2003) and Tarentola (Harris et al, 2004b) all show deep phylogenetic divisions, and the same is demonstrated here in U. acanthinura.…”
Section: Resultssupporting
confidence: 69%
“…However, double-digit values of % sequence divergence within molluscan populations, such as those shown in Figs 3 and 4, are not entirely unprecedented. The phenomenon has been reported within numerous populations of land snails (Thomaz et al 1996, Goodacre and Wade 2001, Guiller et al 2001, Haase et al 2003 and in the special case of doubly-uniparental inheritance in bivalves (Rawson …”
Section: Discussionmentioning
confidence: 82%
“…As a consequence, we expect that at least some dating events proposed for the recently introduced populations across the Mediterranean Basin are likely overestimated. It is thus especially surprising that those estimates that predated by far evidences of human crossing of the Strait of Gibraltar or fossil records were not envisaged under the light of these expected estimation biases and limitations (Guiller et al 2001;Libois et al 2001;Michaux et al 2003;Brandli et al 2005;Cosson et al 2005). Recent methods that calculate simultaneously times of divergence, population sizes and migration rates, were designed to circumvent this bias (e.g.…”
Section: Translocation Scenarios and Historical Demography Of The Eurmentioning
confidence: 99%